Uptake of early infant HIV diagnosis and its associated factors in Tanzania: an analytical cross-sectional study - Esther Gaudence Kiurugo; Saada Ali Seif; Walter Cleo Milanzi (AIDS Research and Therapy, 2024)
Abstract The uptake of early infant HIV diagnosis services is crucial for preventing mother to child transmission of virus, and timely management. However, the uptake of the services remains a global challenge, despite major advances in HIV testing. This study investigated the uptake of early infant HIV diagnosis and its associated factors among mothersof exposed infants. The results showed that the uptake of early infant HIV diagnosis was 76%. Factors associated with the uptake are caregivers being married, have higher income level and having adequate knowledge on early infant HIV diagnosis.